1976
DOI: 10.1210/jcem-43-5-1036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethinylestradiol on the Renin- Angiotensin-Aldosterone-System and on Plasma Transcortin in Women and Men*†

Abstract: The effects of ethinylestradiol (1 mug/kg body weight daily) on plasma renin substrate concentration, other factors of the renin-aldosterone-system, and on the cortisol-binding capacity of transcortin were determined in 8 young men and 9 young women. The absolute and relative elevation of plasma renin substrate after 5, 14, and 24 days of ethinylestradiol administration was significantly (P less than 0.001) greater in females than males. Control and posttreatment transcortin levels were also higher in women th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
5
9
0
Order By: Relevance
“…A promoter region in the angiotensinogen gene is responsive to estrogen (31). Ingestion of ethinyl estradiol as part of an OC results in increases in plasma angiotensinogen to levels only marginally less than those seen in pregnancy (32). In the present study, we observed that a clear difference exists between OC users and control subjects in the systemic and renal hemodynamic response to Ang II infusion, with OC users exhibiting increased responsiveness to Ang II infusion.…”
Section: Discussionsupporting
confidence: 45%
“…A promoter region in the angiotensinogen gene is responsive to estrogen (31). Ingestion of ethinyl estradiol as part of an OC results in increases in plasma angiotensinogen to levels only marginally less than those seen in pregnancy (32). In the present study, we observed that a clear difference exists between OC users and control subjects in the systemic and renal hemodynamic response to Ang II infusion, with OC users exhibiting increased responsiveness to Ang II infusion.…”
Section: Discussionsupporting
confidence: 45%
“…19,20 Indeed, this activation of the RAAS has been proposed as a potential mechanism of estrogen-associated hypertension. Transdermal estrogen avoids this effect on the liver, and no effect on PRA or aldosterone has been shown in this and prior studies.…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…In two studies (10,15), a differential BP response to oral and transdermal estrogen has been described, demonstrating that transdermal HRT reduces ABP, but oral HRT does not affect office BP. A possible mechanism responsible for this finding is that oral estrogens increase hepatic expression of angiotensinogen (34,35). The hepatic effect of transdermally delivered estrogen, in which first liver passage effects are avoided, is less pronounced than that of oral estrogen, and no significant increase in the renin-substrate concentration has been observed (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen increases prostacyclin production (38), endothelium-dependent vasodilation (39), calcium channel blockade (40), and bradykinin production (20)(21)(22). Previous studies using oral estrogen have demonstrated increases in plasma renin activity and aldosterone concentration, likely through a hepatic-induced increase in angiotensinogen production (34,35). Our previous study also showed increases in the plasma angiotensin II and bradykinin concentrations in hypertensive postmenopausal women, suggesting that an estrogen-induced increase in angiotensin II may be balanced by an increase in bradykinin to maintain BP (22).…”
Section: Discussionmentioning
confidence: 99%